2010
DOI: 10.1093/aob/mcq252
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary diversification and geographical isolation in Dubautia laxa (Asteraceae), a widespread member of the Hawaiian silversword alliance

Abstract: These results indicate that geographical separation has aided diversification in D. laxa, whereas ecologically associated morphological differences are not associated with neutral genetic differentiation. This suggests that, despite the stunning ecological adaptation observed, geography has also played an important role in the Hawaiian silversword alliance plant adaptive radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 68 publications
4
22
0
Order By: Relevance
“…(), studying orchid populations ( Epidendrum secundum ) sympatric with Ameroglossum , found evidence only for IBD when analysing plastid microsatellites but for neither IBD nor IBE when analysing nuclear microsatellites, indicating genetic homogenisation among populations through gene flow by pollen. Unique signs of IBD driving populations and species divergence in island‐systems have been found in a member of the Hawaiian silversword alliance ( Dubautia laxa ) and in sister‐species of Primulaceae from sky‐islands in Europe (Boucher et al., ; McGlaughlin & Friar, ). Similar to Ameroglossum , a combination of IBD and IBE associated with genetic variation within and between species from isolated habitat patches was found for Argyroderma in the Cape Floristic Region of South Africa (Ellis et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), studying orchid populations ( Epidendrum secundum ) sympatric with Ameroglossum , found evidence only for IBD when analysing plastid microsatellites but for neither IBD nor IBE when analysing nuclear microsatellites, indicating genetic homogenisation among populations through gene flow by pollen. Unique signs of IBD driving populations and species divergence in island‐systems have been found in a member of the Hawaiian silversword alliance ( Dubautia laxa ) and in sister‐species of Primulaceae from sky‐islands in Europe (Boucher et al., ; McGlaughlin & Friar, ). Similar to Ameroglossum , a combination of IBD and IBE associated with genetic variation within and between species from isolated habitat patches was found for Argyroderma in the Cape Floristic Region of South Africa (Ellis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although some studies have shown that the significance of geographic and environmental isolation varies among types of islands (e.g. Boucher et al., ; Ellis et al., ; McGlaughlin & Friar, ), their relative contributions have not been quantified. Therefore, the roles of these types of isolation in population and species divergence in terrestrial‐island systems remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the S. menziesii- S. salicaria hybrid zone discussed here, Willyard et al [43] uncovered several instances of cryptic chloroplast introgression throughout Schiedea . As expected of recently evolved systems, many of these hybridization events occur between species that are not widely divergent genetically [44], and ecological barriers are typically stronger than genetic barriers to gene flow [39], [45]. Given the increased detection of interspecific hybridization in continental and island plant systems, a more detailed understanding of the adaptive nature of hybridization [46] is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Mort et al, 2002;McGlaughlin & Friar, 2011;Wallace et al, 2011). The coalescence of individual LFY copies within each taxon, long branches between recognized species and concordance of the molecular, morphological and traditional taxonomic data suggest that the LFY gene tree reflects the species tree.…”
Section: Colonizationmentioning
confidence: 99%